'The local mwananchi has lost trust': design, transition and legitimacy in Kenyan election management*. Issue 4 (4th November 2016) - Erlich, Aaron; Kerr, Nicholas
ABSTRACT: Across African democracies, maintaining popular trust in electoral management bodies (EMBs) is vital to enhancing election integrity and, ultimately, regime legitimacy. However, scholars have largely sidestepped any systematic analysis of how citizens formulate their attitudes towards EMBs and how these attitudes vary over time. To address these gaps in the literature, we focus on Kenyan EMBs, which have experienced fluctuating popular support since the ruinous 2007 elections and subsequent institutional reforms. Using primary election reports and original survey and focus group data, we analyse the sources of Kenyans' trust in EMBs from 1992 onward and probe the 2013 election period deeply. Across time, we find that confidence in EMBs usually collapses after polarised elections, due to perceived problems with the EMB's autonomy and capacity. Following the 2013 elections, Kenyans were also more likely to lose confidence in the EMB if they were affiliated with losing presidential candidates or if they were critical of EMB performance.